Flexible and Stretchable Microbatteries for Wearable Technologies. Issue 12 (2nd September 2020) - Nasreldin, Mohamed; de Mulatier, Séverine; Delattre, Roger; Ramuz, Marc; Djenizian, Thierry
Abstract: Soft microbatteries should rapidly emerge on the world market owing to the spectacular rise of wearable technologies that are needed to be powered. The field of applications is actually very large as the main sectors that will be impacted include Internet‐of‐things, printed electronics, e‐textile, medical devices, smart cards, … These specific micropower sources have to show high electrochemical performance and sustain various mechanical strains. They also have to fulfill harsh criteria in terms of size and fabrication processes to ensure their integration in functional devices. In this report, achievements on structural design, fabrication strategies, and performances of flexible and stretchable microbatteries are reviewed. The different strategies proposed to improve electrochemical and mechanical properties: creation of new designs, investigation of alternative microstructuring techniques, involvement of new nanomaterials, etc., are highlighted. The future prospects of these recent technologies are also discussed. Abstract : Different designs and fabrication processes of soft microbatteries for wearable electronics are overviewed. The past and current research and developments of flexible and stretchable micropower sources as well as the various approaches that have been investigated to improve electrochemical and mechanical features are highlighted. The future prospects of these recent technologies are also discussed.